2007
DOI: 10.1111/j.1440-1746.2007.04936.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing incidence of acute pancreatitis: 10‐year experience at the Royal Children's Hospital, Melbourne

Abstract: The incidence of acute pancreatitis in children has increased significantly over the past decade. The increase was greatest in children with idiopathic pancreatitis. It remains unclear whether this reflects a true incidence increase or improved clinical awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
158
3
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 22 publications
10
158
3
12
Order By: Relevance
“…The rate of childhood AP reported here for the UK was lower than that reported for Australia (2.5/100,000 in 1993 and 3.6/100,000 in 2002), 6 and the USA (2.4/100,000 in 1993 and 13.2/100,000 in 2004). 3 However, both of these studies were retrospective reviews conducted at major paediatric referral centres and the cases of AP were detected by either reviewing hospital laboratory databases, 6 or hospital discharge records. 3 The retrospective nature, referral bias and variation in the diagnostic criteria and age groups of these studies may explain these differences.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The rate of childhood AP reported here for the UK was lower than that reported for Australia (2.5/100,000 in 1993 and 3.6/100,000 in 2002), 6 and the USA (2.4/100,000 in 1993 and 13.2/100,000 in 2004). 3 However, both of these studies were retrospective reviews conducted at major paediatric referral centres and the cases of AP were detected by either reviewing hospital laboratory databases, 6 or hospital discharge records. 3 The retrospective nature, referral bias and variation in the diagnostic criteria and age groups of these studies may explain these differences.…”
Section: Discussioncontrasting
confidence: 77%
“…1 AP is uncommon in children, but leads to significant morbidity in the short, medium and long-term. Recently, an increase in the number of paediatric AP cases in single institutions has been reported by centres in the USA, [2][3][4][5] Australia, 6 and Mexico. 7 However, these studies are retrospective reviews and the incidence of AP is usually reported as an absolute number of cases per centre per year at individual referral institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, la mortalidad descrita es de alrededor de un 10% 2,3 . Artículos recientes señalan que la incidencia de la PA en niños ha aumentado en los últimos años 2,4 .…”
Section: Introductionunclassified
“…Actualmente, la mortalidad descrita es de alrededor de un 10% 2,3 . Artículos recientes señalan que la incidencia de la PA en niños ha aumentado en los últimos años 2,4 . Las causas más frecuentes de PA en pediatría son el trauma, las enfermedades sistémicas, el uso de drogas, la PA idiopática y la patología biliar, incluyendo alteraciones anatómicas de la vía biliar y litiasis 2,5,6 .…”
Section: Introductionunclassified
See 1 more Smart Citation